LITERATURE REVIEW: RELATIONSHIP BETWEEN FOOD SECURITY AND STUNTING AMONG TODDLERS - Nathasa Weisdania Sihite (POLTEKKES KEMENKES JAYAPURA, 2022)
Stunting is a condition in children with a length or height of less than -2 SD. Stunting harms children under five and causes growth failure due to chronic nutritional deficiency. In Indonesia in 2017, the prevalence of stunting was 36.4%, which shows the world that Indonesia ranks third as the country with the highest majority of stunting in Southeast Asia. The harmful impact of stunting in the future is a decrease in the quality of human resources, which includes aspects of decreasing the productivity of human resources in the future. Food security is indicated to be one of the factors causing stunting in toddlers, and stunting conditions are closely related to food insecurity experienced by toddlers. This literature review aims to analyze and provide information on the relationship between food security and the incidence of stunting in children under five. The narrative study reviewed many research articles related to food security and the incidence of stunting in children under five. The review results from various sources have been reviewed, showing a close relationship between food security and the incidence of stunting in children under five. Food insecurity experienced by a family directly impacts the food intake of family members to be not optimal both in terms of quantity and quality; this is the cause of the formation of a situation that is not food insecure. The long-term of this condition is that the nutritional adequacy of children under five is not fulfilled, and stunting cannot be prevented. Hopefully, this study can provide information that food adequacy, as seen from food security, is the basis for fulfilling the nutritional needs of children under five. Keywords: Toddler, Food security, Stunting